Functional characterization of Vibrio alginolyticus T3SS regulator ExsA and evaluation of its mutant as a live attenuated vaccine candidate in zebrafish (Danio rerio) model - Zhang, Weijie; Chen, Liangchuan; Feng, Haiyun; Wang, Junlin; Zeng, Fuyuan; Xiao, Xing; Jian, Jichang; Wang, Na; Pang, Huanying (Frontiers in Veterinary Science, 2022)
Vibrio alginolyticus, a Gram-negative bacterium, is an opportunistic pathogen of both marine animals and people, resulting in significant losses in the aquaculture industry. Type III secretion system (T3SS), a crucial virulence mechanism of V. alginolyticus, is closely interconnected with its pathogenicity. In this study, the T3SS regulatory gene exsA, which was cloned from V. alginolyticus wild-type strain HY9901, is 861 bp long encoding a protein of 286 amino acids. The HY9901ΔexsA was constructed by homologous recombination and Overlap-PCR. Although no difference was in growth between HY9901 and HY9901ΔexsA, the HY9901ΔexsA exhibited significantly decreased extracellular protease activity and biofilm formation. Besides, The HY9901ΔexsA showed a weakened swarming phenotype and an approximately 100-fold decrease in virulence to zebraﬁsh. Antibiotic susceptibility testing showed the HY9901ΔexsA was more sensitive to kanamycin, minocycline, tetracycline, gentamicin, doxycycline and neomycin. Compared to HY9901 there were 541 up-regulated genes and 663 down-regulated genes in ΔexsA, screened by transcriptome sequencing. qRT-PCR and β-galactosidase reporter assays were used to analyze the transcription levels of hop gene revealing that exsA gene could facilitate the expression of hop gene. Finally, Danio rerio, vaccinated with HY9901ΔexsA through intramuscular injection, induced a relative percent survival (RPS) value of 66.7% after challenging with HY9901 wild type strain. qRT-PCR assays showed that vaccination with HY9901ΔexsA increased the expression of immune-related genes, including GATA-1, IL6, IgM, and TNF-α in zebraﬁsh. In summary, these results demonstrate the importance of exsA in V. alginolyticus and provide a basis for further investigations into the virulence and infection mechanism.